Assessment of solid waste management practices of households a case study of two selected coastal barangays of Catanauan Municipality, Quezon Province, Philippines - Ali, Mirza Shawkat; Delos Reyes, Mario R. (2001)
Rapid urbanization, along with population increase both by natural increase and in-migration have caused the cities to suffer different inadequancy of infrastructural facilities. Among them solidwaste management is one of the greatest problems of major urban centers, especially due to want of a available suitable space in the vicinity of the city for solid waste disposal. Although the problem are not that acute in smaller towns and cities, if considered from aesthetic and health and hygienic point of view, solid waste management derserves a better consideration, than what is given to it at present by the smaller towns and cities. The purpose of theis study is to identify and analyze the waste disposal practices of households, in rural as well as in the poblacion area. Understanding the practice of waste management, which are handled and managed by Local Government Units(LGUs) and also by the rural community themselves, are the key to understanding the problems and potentials that are available both at the individual, community and municipal level. Similar to most cases in the municipalities all over the Philippines, in the Municipality of Catanauan, solid waste is collected and managed by the LGU only in the poblacion area. This is due to lack of infrastructural facilities, especially road network in the rural areas, lack of sufficient dump trucks to collect the waste and also financial resource constraints. Nevertheless, two barangays in this study, a poblacion and a rural barangay, presented two distinct pictures of the waste management practice by the residents. It is expected that with the increase of population, solid waste management would be a major problem for the municipality. Preventive measures should be given due consideration to remedial measures; especially reuse, recycling and composting of biodegradable materials should be emphasized. Otherwise, if the present trend of solid waste generation and disposal practice continues, the barangays would be a place of unhygienic living condition. The present waste management practice, which is mainly dumping of waste and burning by the municipality, should not be allowed from the national, as well as, the global point of view considering effect on underground water pollution and it harmful effect on ozone layer depletion. From the analysis and findings, two strategies have been advocated. One, is waste minimization as a strategy to reduce the pressure of increased waste transportation and disposal. This transportation and management can be managed solely by the LGU. The other one is the sharing of burden through joint management by the individuals, communities, NGOs and the municipality at household, community and municipal level respectively. In addition, information and education campaign was identified as the prime mover of changing the present concept of burning and future minimization of waste generation in botyh the poblacion and the rural barangays. It was also felt that Barangay Captains should be involved to improve the community waste management at the household level, especially at the rural barangays.Considering the weak economic base and limited resources of the municipality, it is impossible for the municipality to bear the solid waste management expenses alone without imposing service charge on the residents. If service charge is imposed, the collected amount along with the municipal budget for the sector may contribute to a better service delivery and greater area coverage.Political commitment and implementation of the locally passed resolutions may result in the improvement of better solid waste management in the municipality. All these measures may bring the change in health and environment, which will usher better and cleaner environment and hygienic living conditions for the Municipality of Catanauan.
Thesis (M.S. Regional Development Planning)--University of the Philippines, Diliman.
Keywords: Refuse and refuse disposal -- Philippines -- Catanauan (Quezon) -- Case studies